Kualitas Pelayanan Kenaikan Pangkat Pegawai Negeri Sipil Oleh Badan Kepegawaian Daerah Kabupaten Gunung Mas - Handayani, Indah Tri (Anterior Jurnal, 2015)
Good governance developments in Indonesia, further encouraging improvements in many areas of government in Indonesia. One important thing that can be done in the development of good governance is the renewal of the public service. One of the values of good governance is essential to be implemented in the public service is service quality. As with any promotion services provided by the Regional Employment Board of Gunung Mas, good service quality are the expectations of the service users are civil servants who proposed the promotion. Research, seminars and writings of experts on service delivery promotion of civil servants are good quality and havemany. The issue of promotion services qualified civil servants are still not running as it shauld. For the research conducted at the Regional Employment Board Gunung Mas is to see how the quality of service of civil servants promotions given and what are the constraints in service promotion. The maincore of service delivery promotion of civil servants is the timeliness quality of service, things that need to be considered here related to the waiting time and processing time, then the accuracy of service, relating to service reliability and error-free service as well as Ease of Getting Care, associated with a service, a serving officer/administrative staff, support facilities are like computers and others.